Review of comparative LCAs of food waste management systems – Current status and potential improvements - Bernstad, A.; la Cour Jansen, J. (Waste management (Elmsford), 2012)
► GHG-emissions from different treatment alternatives vary largely in 25 reviewed comparative LCAs of bio-waste management. ► System-boundary settings often vary largely in reviewed studies. ► Existing LCA guidelines give varying recommendations in relation to several key issues. Twenty-five comparative cycle assessments (LCAs) addressing food waste treatment were reviewed, including the treatment alternatives landfill, thermal treatment, compost (small and large scale) and anaerobic digestion. The global warming potential related to these treatment alternatives varies largely amongst the studies. Large differences in relation to setting of system boundaries, methodological choices and variations in used input data were seen between the studies. Also, a number of internal contradictions were identified, many times resulting in biased comparisons between alternatives. Thus, noticed differences in global warming potential are not found to be a result of actual differences in the environmental impacts from studied systems, but rather to differences in the performance of the study. A number of key issues with high impact on the overall global warming potential from different treatment alternatives for food waste were identified through the use of one-way sensitivity analyses in relation to a previously performed LCA of food waste management. Assumptions related to characteristics in treated waste, losses and emissions of carbon, nutrients and other compounds during the collection, storage and pretreatment, potential energy recovery through combustion, emissions from composting, emissions from storage and land use of bio-fertilizers and chemical fertilizers and eco-profiles of substituted goods were all identified as highly relevant for the outcomes of this type of comparisons. As the use of LCA in this area is likely to increase in coming years, it is highly relevant to establish more detailed guidelines within this field in order to increase both the general quality in assessments as well as the potentials for cross-study comparisons.